Answer:
-2, -4, -3 + 2i, -3-2i
Step-by-step explanation:
Equaling the function to zero we have:
(x ^ 2 + 6x + 8) (x ^ 2 + 6x + 13) = 0
For the first parenthesis we have:
(x ^ 2 + 6x + 8) = 0\\(x + 4) (x + 2) = 0
Therefore the roots are:
x = - 4\\x = - 2
For the second parenthesis we have:
(x ^ 2 + 6x + 13) = 0
By completing squares we have:
x ^ 2 + 6x = -13
x ^ 2 + 6x + (\frac{6}{2}) ^ 2 = -13 + (\frac{6}{2}) ^ 2\\x ^ 2 + 6x + 9 = -13 + 9\\(x + 3) ^ 2 = - 4\\x + 3 = +/- \sqrt{-4}
Therefore the roots are:
x = -3 + 2i\\x = -3 - 2i
Hope this was helpful
Y - y1 = m(x - x1)
y + 7 = (-1/8)(x - 9)
y + 7 = (-1/8)x + 1.125
Subtract 7 from both sides
y = -1/8x - 5.875
Answer:
17.84875
Step-by-step explanation:
5.45 x 3.275 = 17.84875
Answer:
All of the following statements are true because the products, three or four numbers, remain the same regardless of how the numbers are grouped.